2016
DOI: 10.1007/s00894-016-2954-8
|View full text |Cite
|
Sign up to set email alerts
|

N–H bond cleavage of ammonia on graphene-like B36 borophene: DFT studies

Abstract: Ammonia N-H bond cleavage at metal-free substrates has attracted great attention because of its industrial importance. Here, we investigate the dissociative adsorption of ammonia onto the surface of a B36 borophene sheet by means of density functional theory calculations. We show that the N-H bond may be broken at the edges of B36 even at room temperature, regarding the small energy barrier of 14.1-19.3 kcal mol(-1) at different levels of theory, and more negative Gibbs free energy change. Unlike basis set siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(13 citation statements)
references
References 39 publications
4
9
0
Order By: Relevance
“…1. In accordance with previous experimental [42] and theoretical [46] reports, the B 36 is not completely planar and has slightly bowl shape with a central hexagonal hole. It is clear that five categories of B atom can be recognized in the structure of B 36 (they are shown in Fig.…”
Section: Properties Of B 36supporting
confidence: 92%
“…1. In accordance with previous experimental [42] and theoretical [46] reports, the B 36 is not completely planar and has slightly bowl shape with a central hexagonal hole. It is clear that five categories of B atom can be recognized in the structure of B 36 (they are shown in Fig.…”
Section: Properties Of B 36supporting
confidence: 92%
“…The bowl-shaped B 36 nanocluster with a central hexagonal hole, exhibits different B-B bond lengths. This structure is exactly accordance with some previous studies [16,20,22,39]. They indicated that the length of 1.6 Å is related to the shortest bond, while the other B-B bonds are slightly longer (1.7 Å).…”
Section: Pristine B 36 Nanocluster and Sa Molecule Geometry Optimizations In Gas Phase And Water Mediumsupporting
confidence: 93%
“…Our results have a little difference with their results due to differences in the method used. Rostami et al show that the HOMO, LUMO, and energy gap depend strongly on the type of density functional used [22]. But they confirmed our method in their investigation.…”
Section: Pristine B 36 Nanocluster and Sa Molecule Geometry Optimizations In Gas Phase And Water Mediumsupporting
confidence: 52%
See 1 more Smart Citation
“…Because of its physical, chemical, optical, and thermal properties, borophene makes its way in countless research interests such as alkali metal ion batteries, Li-S batteries, hydrogen storage, supercapacitors, sensors, catalytic hydrogen evolution, oxygen reduction or evolution, CO 2 electro reduction cause and effects [36].…”
Section: Introductionmentioning
confidence: 99%